Values and impacts as precursors for measuring library returns on investment: the case of Covenant University Library in South-West Nigeria (2019)
The study assessed values and impacts as precursors for measuring library returns on investment at Covenant University. This was with the aim of determining the extent to which users visit the library, the extent of staff familiarity with library users’ services, the level of impact of the library on the clientele, institution and community as well as preferred means of communication for both students and staff. Descriptive survey design was adopted for the study. The population of the study consisted of librarians and academic Staff. Simple random sampling technique was used to select 437 academic Staff and 18 professional librarians. Instruments for data collection included questionnaire, institution/library records and reports. The data was analysed using frequencies and percentages while cross tabulation of variables was used for descriptive statistics as well as Statistical Package for Social Science (SPSS). Findings revealed among others that the library is highly patronized and there is a great impact of the library on its users and community. It concluded that Covenant University library users value the services provided by the library as both print and digital resources were heavily used, there was frequent usage of the physical library and online digital resources. The study recommended that the librarians should be more proactive and continuously engage in promoting the use of library resources, maintain relationship with the library users, engage in orientation and re-orientation for faculty, staff and students, appraise and measure library operations often for informed decisions on enhanced service delivery